2022
DOI: 10.1111/bjep.12529
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' physiological and self‐reported stress, teaching practices and students' learning outcomes in Grade 1

Abstract: Background: Teachers' self-reported stress is related to the quality of teacher-student interactions and students' learning outcomes. However, it is unclear if teachers' physiological stress is related to child-centred teaching practices in the classroom and whether teaching practices mediate the link between teachers' stress and students' learning outcomes. Aims: We studied the effect of teachers' physiological stress and self-reported stress on their teaching practices and thereby on students' learning outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 70 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…Interpretation was limited by age differences between the two groups, the small size especially of the control group ( n = 11), and extreme cases in this group. Finally, Jõgi et al (2022/this issue) assessed first grade classroom teachers' levels of cortisol in the middle of the school morning, slope of cortisol levels from awakening to bedtime, self‐reported chronic levels of stress related to teaching, and child‐ versus teacher‐centred classroom instruction as well as their students' math achievement. Cortisol was assessed on two working days, and instruction was observed during three lessons.…”
Section: Overview Of Major Findingsmentioning
confidence: 99%
“…Interpretation was limited by age differences between the two groups, the small size especially of the control group ( n = 11), and extreme cases in this group. Finally, Jõgi et al (2022/this issue) assessed first grade classroom teachers' levels of cortisol in the middle of the school morning, slope of cortisol levels from awakening to bedtime, self‐reported chronic levels of stress related to teaching, and child‐ versus teacher‐centred classroom instruction as well as their students' math achievement. Cortisol was assessed on two working days, and instruction was observed during three lessons.…”
Section: Overview Of Major Findingsmentioning
confidence: 99%
“…Graham et al (2022/this volume) report associations between students' expectancies for success and a physiological component of test anxiety, salivary cortisol, during an authentic testing set in a sample of undergraduate engineering majors. Jõgi, Pakarinen, et al (2022/this volume) explore both teachers' self‐reported and physiological stress (salivary cortisol) in relation to observed teaching practices and students' math skills in early elementary school. Together, the three studies increase the existing understanding of how different biomarkers of stress are related to students' learning experiences.…”
Section: This Special Issue: the Potential Of Biophysiology For Under...mentioning
confidence: 99%
“…Furthermore, both negative and positive strain [11] promote occupational outcomes [11,12]. While this area of research is largely underexplored in the teaching profession [11], studies with teachers nevertheless suggest links between personal strain and teacher behavior [14,15].…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Inclusive demands, inclusive resources and strain also have consequences for teachers' occupational behaviors and instruction [11]. Currently, international and national studies have shown that negative strain can lead to less student-centered teaching behavior [14], an increase in undisciplined student behavior, an unfavorable classroom climate [57] and low teaching quality [15]. However, there is a lack of research on the effects of strain in inclusive settings.…”
Section: Indented Inclusive Practices As Occupational Outcomementioning
confidence: 99%